Analisis Kualitatif Perilaku Cyberloafing terhadap Pekerja di Lingkungan Kerja - Wiryawan Yurih Kaloko; Diah Priharsari; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The presence of the COVID-19 pandemic has recently changed the way humans work in various fields of work, especially for office workers. This phenomenon makes many companies take full advantage of information technology and the internet in their work environment. This provides comfort for humans to cause various problems, one of which is cyberloafing behavior. In this case, company managers need to consider the impact received from cyberloafing behavior in the work environment. This study aims to investigate more deeply the cyberloafing behavior of workers' use of information technology and the internet. This research hopes that it can contribute to the risk of adopting information technology and the internet into the process of designing a work environment in the field of Information Systems. The results of the study prove that the occurrence of cyberloafing activities is determined by the desire and need for rest at work and the occurrence of this behavior can be influenced by rules and reactions from the company. Then, cyberloafing behavior is also carried out at the same time and is carried out repeatedly, or under certain conditions if the conditions experienced by employees are met. In addition, the employee's view of cyberloafing behavior also has positive or negative values ​​depending on whether it is carried out according to the portion or not, if this behavior is carried out excessively it can have a negative impact on employees and the company.